Facilitating free travel in the Schengen area—A position paper by the European Association for Biometrics - Christoph Busch; Farzin Deravi; Dinusha Frings; Els Kindt; Ralph Lessmann; Alexander Nouak; Jean Salomon; Mateus Achcar; Fernando Alonso‐Fernandez; Daniel Bachenheimer; David Bethell; Josef Bigun; et al. (IET Biometrics)
Abstract Due to migration, terror‐threats and the viral pandemic, various EU member states have re‐established internal border control or even closed their borders. European Association for Biometrics (EAB), a non‐profit organisation, solicited the views of its members on ways which biometric technologies and services may be used to help with re‐establishing open borders within the Schengen area while at the same time mitigating any adverse effects. From the responses received, this position paper was composed to identify ideas to re‐establish free travel between the member states in the Schengen area. The paper covers the contending needs for security, open borders and fundamental rights as well as legal constraints that any technological solution must consider. A range of specific technologies for direct biometric recognition alongside complementary measures are outlined. The interrelated issues of ethical and societal considerations are also highlighted. Provided a holistic approach is adopted, it may be possible to reach a more optimal trade‐off with regards to open borders while maintaining a high‐level of security and protection of fundamental rights. European Association for Biometrics and its members can play an important role in fostering a shared understanding of security and mobility challenges and their solutions.